Lithium ion battery

By using silicon-carbon composite materials, fluorovinyl carbonate and sulfur-containing additives in lithium-ion batteries, the electrochemical performance deterioration caused by expansion and contraction of silicon materials is solved, the energy density and circulation performance are improved, and the overall performance is improved. Electrochemical properties.

CN119170876AInactive Publication Date: 2024-12-20HIGHPOWER TECH HUIZHOU

Patent Information

Application Number
CN202411678563.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Silicon materials in lithium-ion batteries have deteriorated electrochemical performance due to expansion and contraction during metal ions embedded and disengagement, affecting energy density and cycling performance.

Method used

Silicon-carbon composite material is used as the negative electrode active layer, combined with fluorovinyl carbonate and sulfur-containing additives in the electrolyte to form a passivation film with excellent performance, and adjust the silicon element in the negative electrode active layer, the additive in the electrolyte, the positive electrode sheet and the negative electrode The reversible capacity ratio of the chip improves the cycling performance of the battery.

Benefits of technology

It improves the energy density and low-temperature cycling performance of lithium-ion batteries, extends the cycle life of the battery, and enhances the overall electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

In order to solve the problem that electrochemical performance is degraded due to the fact that a secondary battery of silicon-carbon composite particles in the prior art expands and shrinks to a large extent in the metal ion embedding and removing process, the lithium ion battery comprises a positive plate, a negative plate and electrolyte, the negative plate comprises a negative current collector and a negative active layer, and the negative current collector is connected with the negative active layer. The negative active layer comprises a silicon-carbon composite material, the silicon-carbon composite material comprises a silicon element and a carbon element, the electrolyte comprises an additive, and the additive comprises fluoroethylene carbonate and a sulfur-containing additive; the lithium ion battery satisfies the following condition: 0.275 < = ((C + B) * (N / P)) / A. The lithium ion battery provided by the invention meets the following conditions: when ((C + B) * (N / P)) / A is more than or equal to 0.275 and less than or equal to (C + B) * (N / P)), the cycle performance of the lithium ion battery is improved while the energy density of the lithium ion battery is improved, so that the purpose of improving the overall electrochemical performance of the lithium ion battery is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary battery preparation, and in particular relates to a lithium ion battery. Background Art

[0002] As a solution for energy storage and supply, secondary batteries are an important choice to meet the needs of sustainable development. With the continuous expansion of its application fields, the requirements for the energy density of secondary batteries are also increasing. Graphite materials are widely used as traditional negative electrode materials, but their theoretical capacity is limited. In contrast, silicon materials have higher theoretical capacity, abundant sources and low prices, and have the potential to become a new generation of secondary battery materials. However, silicon materials will expand and shrink to a large extent during the insertion and extraction of metal ions, resulting in the degradation of electrochemical properties. Therefore, while improving the energy density, it is necessary to avoid the degradation of other electrochemical properties of secondary lithium-ion batteries to ensure that silicon materials are widely used. Summary of the invention

[0003] Aiming at the problem that secondary batteries of silicon-carbon composite particles in the prior art expand and contract to a large extent during the process of metal ion embedding and extraction, resulting in degradation of electrochemical performance, a lithium ion battery is provided.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer, the negative electrode active layer comprises a silicon-carbon composite material, the silicon-carbon composite material comprises silicon and carbon, the electrolyte comprises an additive, and the additive comprises fluoroethylene carbonate and a sulfur-containing additive; A is the mass percentage of silicon in the negative electrode active layer; B is the mass percentage of fluoroethylene carbonate in the electrolyte; C is the mass percentage of sulfur-containing additives in the electrolyte; P is the reversible capacity of the positive electrode, mA·h / g; N is the reversible capacity of the negative electrode, mA·h / g; The lithium-ion battery meets the following conditions: 0.275≤((C+B)*(N / P)) / A.

[0005] Optionally, the lithium-ion battery meets the following conditions: 0.45≤((C+B)*(N / P)) / A.

[0006] Optionally, the reversible capacity of the positive electrode sheet and the reversible capacity of the negative electrode sheet satisfy the following conditions: 0.8≤N / P≤1.5.

[0007] Optionally, the fluoroethylene carbonate and the sulfur-containing additive in the electrolyte meet the following conditions: 0.05≤C / B.

[0008] Optionally, the mass percentage of silicon element in the negative electrode active layer is A≤20%.

[0009] Optionally, the mass percentage of fluoroethylene carbonate in the electrolyte is 5%≤B≤20%.

[0010] Optionally, the mass percentage of the sulfur-containing additive in the electrolyte is 0.5%≤C≤4%.

[0011] Optionally, the sulfur-containing additive includes at least one of the following compounds: .

[0012] Optionally, the electrolyte further comprises an organic solvent and an electrolyte salt; Taking the total mass of the electrolyte as 100%, the mass percentage of the organic solvent is 50% to 90%.

[0013] Optionally, the electrolyte salt includes one or more of lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiODFB, lithium bis(oxalatoborate) LiBOB, lithium difluorobis(oxalatophosphate) LiDFOP, lithium tetrafluoroborate LiBF4, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI and lithium difluorophosphate LiPOF2; The concentration of the electrolyte salt is 0.4 mol / L~2.2 mol / L.

[0014] Optionally, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0015] The beneficial effects of the present invention are: The lithium ion battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte comprises an additive, wherein the additive comprises fluoroethylene carbonate and a sulfur-containing additive, wherein the fluoroethylene carbonate and the sulfur-containing additive can form a passivation film with excellent performance on the surface of the positive and negative electrodes, which is beneficial to improving the cycle performance of the lithium ion battery; the negative electrode active layer of the negative electrode sheet comprises a silicon-carbon composite material, and when the silicon-carbon composite material comprises silicon and carbon elements, it combines the high theoretical capacity of silicon with the excellent conductivity and mechanical stability of carbon, which is beneficial to improving the energy density and conductivity of the lithium ion battery, and since the volume expansion effect of the silicon element will continuously consume active lithium and cause a rapid consumption of the additive, at this time, the sulfur-containing additive and the fluoroethylene carbonate in the electrolyte can continuously modify the SEI film to improve the cycle performance of the silicon negative electrode; In addition, the present application finds that the lithium ion battery satisfies the following conditions by adjusting the ratio of silicon element in the negative electrode active layer, fluoroethylene carbonate in the electrolyte, sulfur-containing additives, and the reversible capacity of the positive electrode sheet and the reversible capacity of the negative electrode sheet: when 0.275≤((C+B)*(N / P)) / A, as the ratio of the reversible capacity of the negative electrode sheet to the reversible capacity of the positive electrode sheet increases, the low-temperature cycle performance of the lithium ion battery is improved. This is because when the capacity of the negative electrode side is higher, it is conducive to accepting lithium ions from the positive electrode side, which can significantly improve the lithium deposition of the lithium ion battery at low temperature, thereby improving the low-temperature cycle performance of the secondary lithium ion battery containing silicon-carbon composite particles; in summary, when the lithium ion battery provided by the present application can improve the cycle performance of the lithium ion battery while increasing the energy density of the lithium ion battery, so as to achieve the purpose of improving the overall electrochemical performance of the lithium ion battery. DETAILED DESCRIPTION

[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0017] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer, the negative electrode active layer comprises a silicon-carbon composite material, the silicon-carbon composite material comprises silicon and carbon, the electrolyte comprises an additive, and the additive comprises fluoroethylene carbonate and a sulfur-containing additive; A is the mass percentage of silicon in the negative electrode active layer; B is the mass percentage of fluoroethylene carbonate in the electrolyte; C is the mass percentage of sulfur-containing additives in the electrolyte; P is the reversible capacity of the positive electrode, mA·h / g; N is the reversible capacity of the negative electrode, mA·h / g; The lithium-ion battery meets the following conditions: 0.275≤((C+B)*(N / P)) / A.

[0018] It should be noted that after the secondary lithium-ion battery containing silicon-carbon composite particles undergoes cycling, the volume of the silicon-carbon composite particles expands and contracts significantly, causing the conductive agent to move with the expansion of the silicon-carbon composite particles, and the displacement of the conductive agent cannot be completely restored with the contraction of the silicon-carbon particles, causing the conductive network inside the negative electrode to be broken. At the same time, the conductivity of silicon itself is worse than that of graphite. Therefore, the low-temperature fast charging performance of the secondary lithium-ion battery containing silicon-carbon composite particles is poor. At the same time, due to the large expansion and contraction of the volume of the silicon-carbon composite particles, the SEI film structure of the negative electrode is constantly destroyed, and the SEI film is reconstructed to consume active lithium, resulting in the attenuation of the cycle performance of the lithium-ion battery, especially at high temperatures. Due to the instability of the SEI film on the silicon negative electrode side, it is easy to cause the SEI film to decompose and produce gas during high-temperature storage. The HF generated by the decomposition of the electrolyte at high temperature will etch silicon and react with silicon, resulting in deterioration of storage performance.

[0019] The lithium ion battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte comprises an additive, wherein the additive comprises fluoroethylene carbonate and a sulfur-containing additive, wherein the fluoroethylene carbonate and the sulfur-containing additive can form a passivation film with excellent performance on the surface of the positive and negative electrodes, which is beneficial to improving the cycle performance of the lithium ion battery; the negative electrode active layer of the negative electrode sheet comprises a silicon-carbon composite material, and when the silicon-carbon composite material comprises silicon and carbon elements, it combines the high theoretical capacity of silicon with the excellent conductivity and mechanical stability of carbon, which is beneficial to improving the energy density and conductivity of the lithium ion battery, and since the volume expansion effect of the silicon element will continuously consume active lithium and cause a rapid consumption of the additive, at this time, the sulfur-containing additive and the fluoroethylene carbonate in the electrolyte can continuously modify the SEI film to improve the cycle performance of the silicon negative electrode; In addition, the present application finds that the lithium ion battery satisfies the following conditions by adjusting the ratio of silicon element in the negative electrode active layer, fluoroethylene carbonate in the electrolyte, sulfur-containing additives, and the reversible capacity of the positive electrode sheet and the reversible capacity of the negative electrode sheet: when 0.275≤((C+B)*(N / P)) / A, as the ratio of the reversible capacity of the negative electrode sheet to the reversible capacity of the positive electrode sheet increases, the low-temperature cycle performance of the lithium ion battery is improved. This is because when the capacity of the negative electrode side is higher, it is conducive to accepting lithium ions from the positive electrode side, which can significantly improve the lithium deposition of the lithium ion battery at low temperature, thereby improving the low-temperature cycle performance of the secondary lithium ion battery containing silicon-carbon composite particles; in summary, when the lithium ion battery provided by the present application can improve the cycle performance of the lithium ion battery while increasing the energy density of the lithium ion battery, so as to achieve the purpose of improving the overall electrochemical performance of the lithium ion battery.

[0020] In some embodiments, the lithium-ion battery satisfies the following condition: 0.45≤((C+B)*(N / P)) / A.

[0021] It should be noted that when the relative ratio of the sulfur-containing additive, fluoroethylene carbonate, the reversible capacity of the negative electrode sheet / the reversible capacity of the positive electrode sheet (N / P) and the silicon content is too small, it is not conducive to improving the cycle performance and high-temperature storage performance of the lithium-ion battery. This is because at a higher silicon content, the volume expansion effect of the silicon element will continuously consume active lithium, thereby causing a sharp consumption of the additive.

[0022] Specifically, adding sulfur-containing additives and fluoroethylene carbonate to the electrolyte of the lithium-ion battery can continuously modify the SEI film to improve the cycle performance of the silicon negative electrode. In addition, due to the poor conductivity of silicon, when N / P is large, the low-temperature cycle performance of the lithium-ion battery can be improved; that is, by controlling the ratio between the silicon element in the negative electrode active layer, the fluoroethylene carbonate in the electrolyte, the sulfur-containing additive, and the reversible capacity of the positive electrode sheet and the reversible capacity of the negative electrode sheet, it is found that the lithium-ion battery meets the following conditions: when 0.45≤((C+B)*(N / P)) / A, the comprehensive performance of the lithium-ion battery can be better improved.

[0023] In some embodiments, the reversible capacity of the positive electrode sheet and the reversible capacity of the negative electrode sheet satisfy the following conditions: 0.8≤N / P≤1.5.

[0024] Specifically, when the N / P ratio is controlled within a suitable range of 0.8≤N / P≤1.5, the low-temperature cycle performance and high-temperature cycle performance of the lithium-ion battery can be well balanced.

[0025] The N / P ratio may be 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4 or 1.5.

[0026] In some embodiments, the fluoroethylene carbonate and the sulfur-containing additive in the electrolyte satisfy the following conditions: 0.05≤C / B.

[0027] Specifically, when the content of the sulfur-containing additive is too low compared to that of fluoroethylene carbonate, it cannot exert the best synergistic effect to improve the performance of the lithium-ion battery. The inventors of the present application have previously verified through a large number of experiments that in the present application, when 0.05≤C / B, the sulfur-containing additive and fluoroethylene carbonate are used in combination to exert a better synergistic effect.

[0028] Specifically, in a preferred embodiment, the C / B value of fluoroethylene carbonate and the sulfur-containing additive in the electrolyte of the present application can be 0.063, 0.125, 0.25, 0.375, 0.5, 0.2, 0.1, 0.083, 0.067, 0.059 or 0.05.

[0029] In some embodiments, the mass percentage of silicon in the negative electrode active layer is A≤20%.

[0030] Since the silicon negative electrode expands greatly during the cycle process, when the silicon content continues to increase, the cycle performance and storage performance of the lithium-ion battery deteriorate, causing the SEI film to continuously break and reconstruct and consume active lithium. When the mass percentage of silicon in the negative electrode active layer exceeds a certain range, the performance of the lithium-ion battery deteriorates sharply.

[0031] Specifically, in order to balance the energy density and performance of lithium-ion batteries, the present application has empirically verified that controlling the mass percentage of silicon in the negative electrode active layer to be between A≤20% is beneficial to improving the cycle performance and storage performance of lithium-ion batteries.

[0032] The mass percentage of silicon element may be 5%, 10%, 15%, 20%, or any value within the above-defined range, which is not limited in the present application.

[0033] In some embodiments, the mass percentage of fluoroethylene carbonate in the electrolyte is 5%≤B≤20%.

[0034] When the mass percentage of fluoroethylene carbonate in the electrolyte additive is too low, it cannot provide good protection for the silicon negative electrode. When the proportion of fluoroethylene carbonate is too high, the cycle performance will deteriorate. This is because too high an additive content will increase the viscosity of the electrolyte, resulting in poor rate performance of the lithium-ion battery. At the same time, fluoroethylene carbonate is easily decomposed and produces gas under high-temperature storage.

[0035] Specifically, in the embodiments of the present application, the mass percentage of fluoroethylene carbonate in the electrolyte can be 5%, 8%, 10%, 12%, 15%, 20% or any value within the above-defined range, and the present application does not impose any limitation on this.

[0036] In some embodiments, the mass percentage of the sulfur-containing additive in the electrolyte is 0.5%≤C≤4%.

[0037] When the proportion of the sulfur-containing additive in the electrolyte is too low, it cannot play a good protective role and improve the storage gas production effect; when the proportion of the sulfur-containing additive in the electrolyte is too high, the cycle performance will deteriorate. At this time, the excessive additive content will increase the viscosity of the electrolyte, resulting in poor rate performance of the lithium-ion battery.

[0038] Specifically, in the embodiments of the present application, the mass percentage of the sulfur-containing additive in the electrolyte can be 0.5%, 1%, 2%, 3%, 4% or any value within the above-defined range, and the present application does not impose any limitation on this.

[0039] In some embodiments, the sulfur-containing additive includes at least one of the following compounds: .

[0040] In some embodiments, the electrolyte further comprises an organic solvent and an electrolyte salt; Taking the total mass of the electrolyte as 100%, the mass percentage of the organic solvent is 50% to 90%.

[0041] In some embodiments, the electrolyte salt includes one or more of lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiODFB, lithium bisoxalatoborate LiBOB, lithium difluorobisoxalatophosphate LiDFOP, lithium tetrafluoroborate LiBF4, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, and lithium difluorophosphate LiPOF2; The concentration of the electrolyte salt is 0.4 mol / L~2.2 mol / L.

[0042] In some embodiments, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0043] Specifically, in a preferred embodiment, the organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC) and diethyl carbonate (DEC).

[0044] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on the positive electrode current collector, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes LiNi a Co b Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is at least one of Al, Mg, Zr and Ti.

[0045] The coating surface density of the positive electrode active layer refers to the mass of the positive electrode active material coated per unit area when coated on one side, and the content of nickel in the positive electrode active material refers to the content of LiNi a Co b Mn (1-a-b) M c The molar percentage or mass percentage of nickel in O2.

[0046] In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which may be any known material suitable for use as a positive electrode current collector; the positive electrode current collector is selected from any one of metal materials or carbon materials including aluminum, stainless steel, nickel plating, titanium, tantalum, etc.; preferably, the positive electrode current collector is a metal material.

[0047] In one embodiment, the positive electrode active layer also includes a conductive agent, a binder and a solvent; the conductive agent includes at least one of natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene; the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.

[0048] In some embodiments, the lithium-ion battery further includes a separator, and the separator is placed between the positive electrode sheet and the negative electrode sheet to prepare a lithium-ion battery.

[0049] In the embodiments of the present application, there is no particular restriction on the material and shape of the diaphragm, as long as it does not significantly impair the effect of the present application; the diaphragm includes a porous sheet or non-woven fabric-like material with excellent liquid retention, and the material of the resin or glass fiber diaphragm includes but is not limited to polyolefins, aromatic polyamides, polytetrafluoroethylene, and polyethersulfone.

[0050] In some implementations, the lithium-ion battery may further include an outer packaging, and the outer packaging of the lithium-ion battery may be used to encapsulate the corresponding electrode assembly and the electrolyte.

[0051] In some implementations, the outer packaging of the lithium-ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell; it can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic. Examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0052] The present application has no particular restriction on the shape of the lithium-ion battery, which may be cylindrical, square or any other shape; the embodiments of the present application have no particular restriction on the negative electrode collector, which may specifically be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0053] Another embodiment of the present invention provides an electrochemical device including the lithium-ion battery.

[0054] Specifically, the electrochemical device including the lithium-ion battery provided by the present invention can be used for, but not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, and energy storage systems.

[0055] The present invention is further described below by way of examples.

[0056] Table 1

[0057] Example 1 This embodiment is used to illustrate the lithium ion battery and electrochemical device disclosed in the present invention, and includes the following operating steps: Preparation of positive electrode: The positive electrode active material LCO, the conductive agent acetylene black (SuperP) and the polyvinylidene fluoride (PVDF) binder are mixed evenly in a mass ratio of 97:1.5:1.5, and evenly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the positive electrode sheet.

[0058] Preparation of negative electrode sheet: The negative electrode active materials graphite and silicon carbon particles, the conductive agent acetylene black (Super P), the thickener CMC and the binder SBR are mixed evenly in a mass ratio of 94:2:1.2:2.8, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the negative electrode sheet.

[0059] Prepare electrolyte: a. Ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) were mixed and stirred in a mass ratio of 10:20:40:30 to form a mixed solvent, and water was removed by molecular sieve for later use, and 1M LiPF6 was added and mixed evenly; b. Add additives to the colorless transparent liquid obtained in step a (the types and amounts of the additives are shown in Table 1) to obtain the electrolytes of the embodiments and comparative examples.

[0060] Assembling lithium-ion batteries: The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets, and the bare cell is obtained by winding and welding the tabs. The bare cell is encapsulated in an aluminum-plastic film to obtain a lithium-ion battery. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrodes to play an isolation role, and then wound to the bare cell. The bare cell is placed in an outer packaging bag, dried at high temperature until the water content of the electrode sheet is less than 100ppm, and the electrolyte prepared above is injected. After vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery is completed.

[0061] Detecting the reversible capacity of lithium-ion batteries: The fully assembled lithium-ion battery is placed on the test system for constant current charge and discharge test at 0.1C, and the second cycle capacity is taken as the reversible capacity P of the positive electrode; when the positive electrode active material is NCM811, the test potential range is 2.8V to 4.4V; when the positive electrode active material is lithium cobalt oxide, the test potential range is 3.0V to 4.58V; when the positive electrode active material is NCM622, the test potential range is 2.8V to 4.4V; when the positive electrode active material is NCM532, the test potential range is 2.8V to 4.4V. Replace the above positive electrode with a negative electrode, and the test potential range is 0.005V to 0.8V, and the reversible capacity N of the negative electrode can be measured.

[0062] Embodiments 2 to 29 Examples 2 to 29 are used to illustrate the lithium ion battery and electrochemical device disclosed in the present invention, including most of the operations in the examples, except that: The relationship between the type and amount of additives in the electrolyte, the mass percentage of the silicon element and the N / P ratio in the lithium-ion battery is shown in Examples 2 to 29 in Table 1.

[0063] Comparative Examples 1 to 4 This comparative example is used to compare and illustrate the lithium ion battery and electrochemical device disclosed in the present invention, including most of the operations in the examples, except that: The relationship between the type and amount of additives in the electrolyte, the mass percentage of the silicon element and the N / P ratio in the lithium-ion battery is shown in Comparative Examples 1 to 4 in Table 1.

[0064] Performance Testing The following performance tests were performed on Examples 1 to 29 and Comparative Examples 1 to 4 prepared as above: 45℃ cycle test: The test method is: in a 45±2℃ constant temperature box, charge the lithium-ion battery to 4.53V at 1C constant current and constant voltage, cut off the current at 0.05C, and then discharge it to 3V at 1C. Perform multiple charge and discharge cycles under the above conditions, and calculate the capacity retention rate of the battery after 600 cycles, with 5 batteries in each group.

[0065] Capacity retention rate (%) = discharge capacity corresponding to the number of cycles (mAh) / discharge capacity of the third cycle (mAh) * 100%.

[0066] The average value of the capacity retention rate of each group of 5 batteries after different cycles is recorded in Table 1.

[0067] 0℃ cycle test: The test method is: in a 0±2℃ constant temperature box, charge the lithium-ion battery to 4.53V at 1C constant current and constant voltage, cut off the current at 0.05C, and then discharge it to 3V at 1C. Perform multiple charge and discharge cycles under the above conditions, and calculate the capacity retention rate of the battery after 600 cycles, with 5 batteries in each group.

[0068] Capacity retention rate (%) = discharge capacity corresponding to the number of cycles (mAh) / discharge capacity of the third cycle (mAh) * 100%.

[0069] The average value of the capacity retention rate of each group of 5 batteries after different cycles is recorded in Table 1.

[0070] 60℃ storage performance test: The test method is: charge the lithium-ion battery to 4.53V at 1C constant current and constant voltage in a 25±2℃ constant temperature box, with a cut-off current of 0.05C, and test the thickness of the lithium-ion battery (this is the thickness before storage). Place the fully charged cell / battery at (60±2)℃ for 35 days in an open circuit, and then place it at room temperature for 2 hours after 35 days of storage, and test the thickness after storage, and calculate the thickness expansion rate of the lithium-ion battery: Thickness expansion rate = [(thickness after storage - thickness before storage) / thickness before storage] × 100%.

[0071] The test results obtained are entered in Table 2.

[0072] Table 2

[0073] It can be seen from the test results in Table 2 that, compared with Comparative Examples 1 to 3, when fluoroethylene carbonate and sulfur-containing additives are added separately in Comparative Examples 2 to 3, the 0°C cycle and 45°C cycle performance of the battery are improved. This is because fluoroethylene carbonate and sulfur-containing additives can form a passivation film with excellent performance on the surface of the positive and negative electrodes; comparing the test results of Comparative Examples 1 and 2, when fluoroethylene carbonate is added alone, the 60°C storage thickness expansion rate deteriorates. This is because fluoroethylene carbonate itself is unstable at high temperatures, and the negative electrode SEI film formed by fluoroethylene carbonate is easily decomposed and gasified at high temperatures; comparing the data of Comparative Examples 1 and 3, when the sulfur-containing additive is added alone, the 60°C storage is improved. This is because the passivation film formed by the sulfur-containing additive at the interface of the positive and negative electrodes has stronger thermal stability and is not easy to decompose at high temperatures.

[0074] Comparing the data of Examples 1 to 5, it can be seen that with the increase of the content of sulfur-containing additives, the cycle performance and high-temperature storage performance of the battery are improved. This is because the sulfur-containing additives can form a passivation film with excellent performance on the surface of the positive and negative electrodes, and the passivation film has good thermal stability and can significantly improve storage gas production. Comparing the data of Comparative Examples 3 to 4 with the data of Examples 1 to 5, it can be seen that when the sulfur-containing additives are too little, it is not enough to significantly improve the high-temperature storage performance; when the sulfur-containing additives are too high, the viscosity of the electrolyte increases, resulting in deterioration of the battery cycle performance; controlling 0.5%≤C≤4% can better balance the battery performance.

[0075] In Examples 6 to 11, as the content of fluoroethylene carbonate increases, the cycle performance of the battery is improved, because fluoroethylene carbonate can form a passivation film with excellent performance on the surface of the positive and negative electrodes; however, as the content of fluoroethylene carbonate increases, the storage performance deteriorates, because fluoroethylene carbonate itself is unstable at high temperatures, and the negative electrode SEI film formed by fluoroethylene carbonate is easily decomposed and gasified at high temperatures.

[0076] Comparing Comparative Examples 1 to 4 with Examples 1 to 10, when no sulfur-containing additive is added or the sulfur-containing additive is too low in content of fluoroethylene carbonate, the best synergistic effect cannot be exerted to improve the performance of the battery. Only when 0.05≤C / B can the sulfur-containing additive form a good synergistic effect on fluoroethylene carbonate. It can be seen from Examples 1 to 10 that the content of fluoroethylene carbonate should not be too high or too low, that is, 5%≤B≤20% is better; when 0.5%≤C≤4%, 5%≤B≤20%, and 0.05≤C / B are satisfied at the same time, the best synergistic effect of fluoroethylene carbonate and sulfur-containing additive can be exerted.

[0077] From the data of Examples 11 to 15, it can be seen that as the silicon content increases, the cycle performance and storage performance of the battery of Examples 13 to 15 deteriorate compared with Examples 11 to 15. This is because the silicon negative electrode expands greatly during the cycle, causing the SEI film to continuously break and reconstruct and consume active lithium. At the same time, the conductivity of silicon itself is poor, and the cycle performance deteriorates at low temperatures. From the data of 16 to 22, it can be seen that as the N / P ratio increases, the 0°C cycle performance of the battery improves. This is because when the capacity of the negative electrode side is higher, it is conducive to accepting lithium ions from the positive electrode side, which can significantly improve the lithium precipitation of the battery at low temperatures, thereby improving the low-temperature cycle performance.

[0078] It can be seen from the data of Examples 23 to 29 that when the sulfur-containing additive selected is other sulfur-containing compounds limited by the present invention, the improvement effect on the battery is consistent.

[0079] It can be seen from the above specific test data that the present application finds that the lithium-ion battery meets the following conditions by adjusting the ratio of silicon element in the negative electrode active layer, fluoroethylene carbonate in the electrolyte, sulfur-containing additives, and the reversible capacity of the positive electrode sheet and the reversible capacity of the negative electrode sheet: when 0.275≤((C+B)*(N / P)) / A, the energy density of the lithium-ion battery can be increased while improving the cycle performance of the lithium-ion battery, so as to achieve the purpose of improving the comprehensive electrochemical performance of the lithium-ion battery.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer, the negative electrode active layer comprises a silicon-carbon composite material, the silicon-carbon composite material comprises silicon and carbon, and the electrolyte comprises an additive, wherein the additive comprises fluoroethylene carbonate and a sulfur-containing additive; The lithium-ion battery meets the following conditions: 0.275≤((C+B)*(N / P)) / A; A is the mass percentage of silicon in the negative electrode active layer; B is the mass percentage of fluoroethylene carbonate in the electrolyte; C is the mass percentage of sulfur-containing additives in the electrolyte; P is the reversible capacity of the positive electrode, in mA·h / g; N is the reversible capacity of the negative electrode, in mA·h / g.

2. A lithium ion battery according to claim 1, characterized in that: The lithium-ion battery meets the following conditions: 0.45≤((C+B)*(N / P)) / A.

3. A lithium ion battery according to claim 1, characterized in that: The reversible capacity of the positive electrode sheet and the reversible capacity of the negative electrode sheet satisfy the following conditions: 0.8≤N / P≤1.

5.

4. A lithium ion battery according to claim 1, characterized in that: The fluoroethylene carbonate and the sulfur-containing additive in the electrolyte meet the following conditions: 0.05≤C / B.

5. A lithium ion battery according to claim 1, characterized in that: The mass percentage of silicon element in the negative electrode active layer is A≤20%.

6. A lithium ion battery according to claim 1, characterized in that: The mass percentage of fluoroethylene carbonate in the electrolyte is 5%≤B≤20%.

7. A lithium ion battery according to claim 1, characterized in that: The mass percentage of the sulfur-containing additive in the electrolyte is 0.5%≤C≤4%.

8. A lithium ion battery according to claim 1, characterized in that: The sulfur-containing additive comprises at least one of the following compounds: 。 9. A lithium ion battery according to claim 1, characterized in that: The electrolyte also includes an organic solvent and an electrolyte salt; Taking the total mass of the electrolyte as 100%, the mass percentage of the organic solvent is 50% to 90%.

10. A lithium ion battery according to claim 9, characterized in that: The electrolyte salt includes one or more of lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiODFB, lithium bisoxalatoborate LiBOB, lithium difluorobisoxalatophosphate LiDFOP, lithium tetrafluoroborate LiBF4, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI and lithium difluorophosphate LiPOF2; The concentration of the electrolyte salt is 0.4 mol / L~2.2 mol / L.

11. A lithium ion battery according to claim 9, characterized in that: The organic solvent includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and lithium ion batter

    CN110336076A

  • Lithium ion battery

    CN117594876A

  • Electrolyte and secondary battery

    CN118630316A

  • Lithium ion battery

    CN118867129A

Cited By

  • Secondary battery and electric device

    CN119786700A

  • Secondary battery and electric device

    CN119786700B

  • Negative electrode sheet and lithium-ion secondary battery

    WO2026145181A1